PDE4 inhibitors: potential protective effects in inflammation and vascular diseases - Fan, Tianfei; Wang, Wenjing; Wang, Yao; Zeng, Mingtang; Liu, Yi; Zhu, Shuyao; Yang, Lin (Frontiers in Pharmacology, 2024)
Phosphodiesterase 4 (PDE4) inhibitors are effective therapeutic agents for various inflammatory diseases. Roflumilast, apremilast, and crisaborole have been developed and approved for the treatment of chronic obstructive pulmonary disease psoriatic arthritis, and atopic dermatitis. Inflammation underlies many vascular diseases, yet the role of PDE4 inhibitors in these diseases remains inadequately explored. This review elucidates the clinical applications and anti-inflammatory mechanisms of PDE4 inhibitors, as well as their potential protective effects on vascular diseases. Additionally, strategies to mitigate the adverse reactions of PDE4 inhibitors are discussed. This article emphasizes the need for further exploration of the therapeutic potential and clinical applications of PDE4 inhibitors in vascular diseases.